Hill of freedom [videorecording (DVD)] - Hong, Sang-su, 1960-; Hong, Sang-su, 1960-; Kase, Ryo, 1974-; Mun, So-ri; Seo, Young-hwa (Grasshopper Film, 2021)
A Japanese man comes to Seoul to find the Korean woman he fell in love with some years ago.